Development of Flipbook Teaching Materials in Differentiated Learning to Improve Mathematical Problem-Solving Based on Students’ Learning Styles - Tsurayya Azzahira (EduGrows: Education and Learning Review, 2025)
Mathematical problem-solving skills are essential for students to face academic challenges and real-life situations. However, the 2022 PISA results and preliminary observations at MTs Negeri 1 Kota Semarang indicated that these skills were still low, particularly in the topic of Linear Equations in Two Variables (SPLDV). This study aimed to develop a flipbook-based teaching material integrated with differentiated learning by considering students’ learning styles (visual, auditory, and kinesthetic), and to examine its feasibility, readability, effectiveness, and students’ responses. This research employed the Research and Development (R&D) method using Borg & Gall’s model with eighth-grade students of MTs Negeri 1 Kota Semarang as the subjects. Data were collected through observation, interviews, questionnaires, documentation, and pretest-posttest. Data analysis was conducted qualitatively (expert and practitioner validation) and quantitatively (feasibility and readability tests, effectiveness tests using one-sample t-test, independent t-test, paired t-test, N-Gain, and individual mastery test using Actual Mastery Threshold/BTA). The findings showed that the flipbook was highly feasible (91.20%) and very readable (92.10%). The developed teaching module received very good validation (88.75%), while the test instrument demonstrated good to very good validity, reliability, difficulty level, and discrimination power. The experimental class average score increased from 49.12 (pretest) to 67.35 (posttest), while the control class rose from 48.82 to 53.53. Statistical tests revealed significant differences (p < 0.001), with an N-Gain score of 0.73 (high category). In addition, individual mastery was achieved based on BTA, and classical mastery was met since more than 75% of students scored above the minimum criteria. Thus, the developed flipbook-based differentiated learning material was feasible, comprehensible, effective in improving mathematical problem-solving skills, and received very positive responses from students. Keywords: Differentiated Learning; Flipbook; Learning Styles; Mathematical Problem-Solving.